Designer's guide to eurocode 9 : design of aluminium structures EN 1999-1-1 and -1-4 - Höglund, Torsten; Tindall, Philip (Designers' guides to the eurocodes., 2012)
Detailing the requirements for resistance, serviceability, durability & fire resistance in the design of buildings & other civil engineering & structural works in aluminium, this guide provides the user with guidance on the interpretation of standards contained in EN 1999.